2019
DOI: 10.24059/olj.v4i2.1905
|View full text |Cite
|
Sign up to set email alerts
|

Integrating ALN into an Independent Study Distance Education Program: NVCC Case Studies

Abstract: This paper describes eight ALN courses developed under various Sloan Foundation-funded degree program initiatives at Northern Virginia Community College (NVCC) Extended Learning Institute (ELI). These chemistry, engineering, mathematics, and information technology courses offer useful lessons about what makes ALN courses successful. The courses incorporated ALN into an independent study format to increase interaction among learning participants while maximizing learner convenience and flexibility; some courses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…The prosperity of students in independent learning requires control in orchestrating learning speed [17], monitoring learning understanding [18], and making assessments on sundry aspects of the cognition process [19]. In the context of independent learning, students need to be aware of and actively investigate a variety of learning materials [20].…”
Section: Introductionmentioning
confidence: 99%
“…The prosperity of students in independent learning requires control in orchestrating learning speed [17], monitoring learning understanding [18], and making assessments on sundry aspects of the cognition process [19]. In the context of independent learning, students need to be aware of and actively investigate a variety of learning materials [20].…”
Section: Introductionmentioning
confidence: 99%
“…Mas, segundo estes autores, "tudo o que está sendo veiculado é a experiência pessoal do pesquisador com o ensino a distância e a extensão que o ensino se mostrou eficaz". (Canning, 2002;Deubel, 2003;Falk, 1998;Fredericksen, Pickett, Shea, Pelz, Swan, 2000;Schrum, Benson, 2000;Sener, Stover, 2000;Shapley, 2000;Morse, 2003). A quarta categoria de pesquisas é o custo compatível.…”
Section: Formulando Questionamentosunclassified
“…Course satisfaction is a critical component in improving learning achievement in the traditional classroom and the distance education environment. Many researchers have examined the factors that influence student satisfaction in distance education (Canning, 2002;Deubel, 2003;Falk, 1998;Freddolino & Sutherland, 2000;Fredericksen, Pickett, Shea, Pelz, & Swan, 2000;Morse, 2003;Nilles, 2002;Schrum & Benson, 2000;Sener & Stover, 2000;Shapley, 2000;Zhang & Fulford, 1994). Researchers suggested that student satisfaction should be assessed before any learning outcome assessments, for negative reactions could hinder students' abilities to learn.…”
Section: Student Satisfactionmentioning
confidence: 99%